Cytomegalovirus results in poor graft function via bone marrow-derived endothelial progenitor cells - Lv, Weiran; Zhou, Ya; Zhao, Ke; Xuan, Li; Huang, Fen; Fan, Zhiping; Chang, Yuan; Yi, Zhengshan; Jin, Hua; Liang, Yang; Liu, Qifa (Frontiers in Microbiology, 2024)
Poor graft function (PGF), characterized by myelosuppression, represents a significant challenge following allogeneic hematopoietic stem cell transplantation (allo-HSCT) with human cytomegalovirus (HCMV) being established as a risk factor for PGF. However, the underlying mechanism remains unclear. Bone marrow endothelial progenitor cells (BM-EPCs) play an important role in supporting hematopoiesis and their dysfunction contributes to PGF development. We aim to explore the effects of CMV on BM-EPCs and its underlying mechanism. We investigated the compromised functionality of EPCs derived from individuals diagnosed with HCMV viremia accompanied by PGF, as well as after infected by HCMV AD 169 strain in vitro, characterized by decreased cell proliferation, tube formation, migration and hematopoietic support, and increased apoptosis and secretion of TGF-β1. We demonstrated that HCMV-induced TGF-β1 secretion by BM-EPCs played a dominant role in hematopoiesis suppression in vitro experiment. Moreover, HCMV down-regulates Vitamin D receptor (VDR) and subsequently activates p38 MAPK pathway to promote TGF-β1 secretion by BM-EPCs. In conclusion, HCMV could infect BM-EPCs and lead to their dysfunction. The secretion of TGF-β1 by BM-EPCs is enhanced by CMV through the activation of p38 MAPK via a VDR-dependent mechanism, ultimately leading to compromised support for hematopoietic progenitors by BM EPCs, which may significantly contribute to the pathogenesis of PGF following allo-HSCT and provide innovative therapeutic strategies targeting PGF.